Understanding Understanding Religious Belief - Cherry, Christopher (Religious studies, 1974)
I try in this article to shed some light on what it is and what it is not to understand certain kinds of beliefs, of which religious belief is the most prominent instance. Much has been written on the subject, and I make no apologies either for taking for granted a context for discussion, or for disregarding a number of familiar issues. I try, in particular, to explain why a rather curious thesis about understanding religious belief has found wide acceptance when, on the face of it, it cannot possibly be correct. I begin with one or two points about belief; I then take what I hope is a fresh look at two theses about understanding religious belief; and finally I draw some tentative conclusions about puzzlement, understanding and understandability.